Current Issues of Wage Accounting in the Conditions of Economic Modernization - Yusupov Farruh Baxromjonovich (European Science Publishing, 2023)
In this article, the current issues of wage accounting in the conditions of modernization of the economy in our country were analysed. Also, one of the important issues of the organization of accounting in economic entities was the analysis of labour cost accounting. The requirements for the calculation and analysis of labour costs are reflected in the national accounting standards and must be followed without deviation. Accordingly, special attention is now being paid to this issue. The above points indicate that it is important to research the calculation of labour costs in enterprises.
Keywords: Wage expenses, cost accounting, labour costs, social protection, enterprises.